NON-SEA-SALT SULFATE AND NITRATE VARIATIONS IN THE S25 CORE, NEAR THE COASTAL REGION, EAST ANTARCTICA - ワタナベ, コウイチ; サトウ, カズヒデ; カミヤマ, コキチ; モトヤマ, ヒデアキ; ワタナベ, オキツグ; WATANABE, Koichi; SATOW, Kazuhide; KAMIYAMA, Kokichi; MOTOYAMA, Hideaki; WATANABE, Okitsugu (National Institute of Polar Research, 1999)
P(論文) Non-sea-salt sulfate (nssSO_4^<2->) and nitrate (NO_3^-) data in the S25 core in the coastal region on Mizuho Plateau, East Antarctica, have been analyzed. Time series of nssSO_4^<2-> which is mainly derived from marine-biogenic sulfur (DMS), showed not only seasonal variations, but also 4-5 year and about 8 year variations. The result indicates that DMS emission and the transport process of nssSO_4^<2-> may be affected by the Antarctic Circumpolar Wave (ACW), whose initiation is probably associated with El Nino activity. The NO_3 concentrations in the S25 core presented about 11-year variations corresponding to the solar cycle. departmental bulletin paper